Evidence of a role for GTP in the potentiation of Ca(2+)-induced insulin secretion by glucose in intact rat islets. - Meredith, M (1995)
Glucose initiates insulin secretion by closing K(+)-ATP channels, leading to Ca2+ influx (E1); it also potentiates Ca(2+)-induced secretion (E2) when the K(+)-ATP channel is kept open using diazoxide and depolarizing concentrations of K+ are provided. To examine the roles of purine nucleotides in E2, we compared the effects of glucose to those of the mitochondrial fuel monomethylsuccinate. Either agonist could induce E2 accompanied by significant increases in ATP, ATP/ADP ratio, and GTP/GDP ratio; GTP increased significantly only with glucose. Mycophenolic acid (MPA), an inhibitor of cytosolic GTP synthesis, markedly inhibited glucose-induced E2 (either in perifusions or in static incubations) and decreased GTP and the GTP/GDP ratio, but did not alter the ATP/ADP ratio. Provision of guanine (but not adenine) reversed these changes pari passu. In contrast, MPA had no effect on succinate-induced E2, despite generally similar changes in nucleotides. A similar lack of effect of MPA on E2 was seen with a second mitochondrial fuel, alpha-ketoisocaproic acid (KIC). However, in the absence of diazoxide and K+, MPA blunted the secretory effects of either glucose, succinate, or KIC. These studies suggest that GTP plays a role in both glucose and succinate or KIC-induced insulin secretion at a step dependent on mitochondrial metabolism and the K(+)-ATP channel. In addition to mitochondrial effects, glucose appears to have extramitochondrial effects important to its potentiation of Ca(2+)-induced insulin secretion that are also dependent on GTP.